Coronary Sinus Diverticulum Complicating CRT Device Implantation: A case repot - Taimur, Syed Dawood Md.; Mansur, Mahbub; Haq, M Maksumul (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 67-69 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13565